Ergonomic Analisis postur kerja pekerja di pabrik teh hijau Pusat Penelitian Teh dan Kina, Gambung - Natalia Florentin Agapa; Noer Addnina Zahra; Kralawi Sita (Research Institute for Tea and Cinchona, 2018)
Uncomfortable work postures will cause ergonomic problems such as musculoskeletal disorders (MSDs) so that workers feel uncomfortable and work becomes risky and unproductive. This study aims to 1) analyze MSDs complaints of workers at the Green Tea Plant; 2) analyze work posture in green tea processing which has the highest complaints of MSDs; 3) analyze the relationship of individual worker characteristics and MSDs complaints. This study uses a descriptive method with a quantitative approach. This research was conducted at the PPTK Gambung Green Tea Factory. Data collection was carried out by observation and interview techniques using the Nordic Body Map (NBM) questionnaire. Data analysis includes 1) analysis of work posture using the OWAS and RULA methods, and 2) analysis of the correlation with Rank Spearman correlation. The results showed that 1) the highest MSDs complaints occurred at packing stations, 2) from the OWAS and RULA analysis, the work posture that had a very high risk level and needed immediate repairs was the position when putting tea in sacks, leveling tea in sacks, raising sacks to top of the trolly, push the trolly, pull the trolly, lift the sack from the top of the trolly and put the sack on the lowest and top arrangement; 3) there is a relationship between the working period with the type of work, and between the length effective work time with complaints MSDs.